Blastomere morphology, neutral bouyancy salinity, and osmolality as predictive measures of egg viability in milkfish, chanos chanos Forsskal. - Denusta, Pastor Jones T.
Morphological characteristics of blastomeres, neutral buoyancy salinity and osmolality of the eggs were determined and correlated with egg viability parameters to identify possible measures of egg quality in milkfish 36 to 50 egg samples from twelve batches were analyzed for cell symmetry, size, adhesion, margins, and inclusions. There were no significant correlations between hatch rate and mean score for each blastomere characteristics. However, hatched and unhatched eggs were significantly different for the cell inclusion parameter assessed at 4-16- and 32-cell stages., Neutral bouyancy salinity (NBS) and total osmolality (TEO) were taken from 8 batches at 4, 12 and 20-hour post-fertilization. NBS was negatively correlated with percent egg viability at 4, 12 and 20 hours, hatch rate and cumulative survival rate at 12 and 20 hours, and percent normal larvae at 20 hours post-fertilization only. TEO was negatively correlated with percent egg viability, hatching rate and cumulative survival rate at 4, 12 and 20 hours, and with percent normal larvae at 12, and 20 hours after spawning. Results suggest that blastomere inclusions, NBS and TEO taken at 12 and 20 hours post fertilization, can be used as measures of egg quality in milkfish. Eggs with NBS higher than 28 psu and osmolality higher than 567 mOsmol kg raise to the power of negative one were low in cumulative survival rate. It is recommended that further study can be done at more frequent time intervals and on other marine species that have pelagic eggs.